Research into recycling of nickelcobaltcontaining metallurgical wastes by the ecologicallysafe technique of hydrogen reduction - Hryhoriev, Stanislav; Petryshchev, Artem; Shyshkanova, Ganna; Zaytseva, Tetyana; Frydman, Oleksandr; Sergienko, Olga; Ivanchenko, Andrii; Usenko, Elena; Berezhnaya, Olga; Semenchuk, Andrii (Eastern-European Journal of Enterprise Technologies, 2017)
We studied kinetic patterns of hydrogen reduction of the scale of a nickel-cobalt containing precision alloy at a temperature of 673‒1573 K over a period from 0 to 180 minutes. The highest degree of reduction was achieved after thermal treatment at 1273 K – 99 %. This is predetermined by the intensification of reduction processes and a sufficient level of porosity, which ensures satisfactory gas exchange. It was discovered that the starting scale consists mainly of Fe3O4, Fe2O3 and FeO with atoms substituting their alloying elements. The target product of metallization had a sponge-like microstructure and consisted mainly of the solid solution of Co and Ni atoms in γ-Fe and the residual non-reduced Fe3O4 and FeO. The resulting phases had no noticeable susceptibility to sublimation. This has ensured a reduction in the losses of alloying elements while receiving and using the highly-alloyed metallized scale, which was confirmed by experimental- industrial tests. At the same time, recycling of industrial wastes contributes to a reduction in the technogenic intensity of industrial regions and improves ecological safety of the environment